Analyzing Fabric Properties and Short Modeling Through 3D Scanning and Computer Prediction - Gupta, Arjun Ramesh (Journal of Computer Science and Software Applications, 2021)
In this study, a considerable variety of fabrics were categorized into five distinct groups. These fabric samples were utilized to create experimental shorts. By focusing on the cross-sections of the hipline, a correlation analysis was performed to examine the relationship between the sectional shape index and the fabrics' physical and mechanical properties, identifying key influencing factors. Utilizing data from 3D scanning, morphological sections and polar coordinates for each characteristic section were constructed. Subsequently, the differences in the cross-sectional curves were analyzed.